Getting to know ourselves and others through the ABCs : a journey toward intercultural understanding - Finkbeiner, Claudia (Language, literacy, and learning., 2014)
This book is a valuable resource for teachers and other professionals who are looking for a proven way to increase cultural appreciation and awareness. New applications of the ABCs model of Cultural Understanding and Communication are presented and discussed in this new volume, based on studies done in the United States, and Canada and Europe. In this ground-breaking project, the authors describe how the ABCs model complicated and challenged and changed the cultural perceptions of those who participated in it, even those who were initially highly resistant to such possibilities. At the heart of the project is the exchange of narratives - life stories that give insight into the cultural worlds of selves and others. In addition to the narratives, other instruments including the Transcultural Competence Scale (TCC), provide further evidence of the positive impact of the ABCs on participants' receptivity toward cultural differences.In the TRANSABCs project, researchers from both sides of the Atlantic invited teacher candidates, students who will become workplace and other professionals to write an autobiography (A) of themselves from various cultural perspectives, a biography (B) of an individual who is culturally different from themselves along particular dimensions, and to use these documents to conduct cross-cultural comparisons (C) between themselves and the person they interviewed. Furthermore, candidates developed culturally responsive ideas for the school or the workplace (C). These exchanges and analyses produced epiphanies and insights that translated into specific actions to improve cultural understanding and communication in classrooms and workplaces. Educators and professionals can take from these examples to inspire their own personal journey toward greater cultural understanding and sensitivity.